Development of IPAS Smart Light Properties Box (Kosifcas) Trainer to Improve Scientific Thinking Ability - Munirul ‘Izzah; Desi Wulandari (Postgraduate, University of Mataram, 2025)
This study aims to develop and test the effectiveness of Smart Light Properties Box (Kosifcas) learning media in improving the scientific thinking ability of fifth grade students of SDN Grogolan Boyolali on light and its properties. This research uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of needs analysis, media design, prototype development, implementation in learning, and effectiveness evaluation. The validation results show that Kosifcas is very feasible to use, with a feasibility score of 95% for media experts and 93% for material experts, resulting in an average of 94% (very feasible category). The small group trial showed a positive response with a 100% acceptance rate, while the large group trial obtained a 100% response from teachers and 98% from students. The effectiveness of this media is reflected in the improvement of learning outcomes, with an average pretest score of 47 (low category) increasing to 86.75 (high category) on the posttest. The t-test showed a significance of 0.001 (<0.05), indicating a significant difference before and after the use of the media. The N-Gain value of 0.7452 (high category) and the N-Gain percentage of 74.52% indicate high effectiveness. Thus, Kosifcas proved to be effective in improving students' understanding of the concept of light and its properties.